Decreased influenza activity during the COVID‐19 pandemic—United States, Australia, Chile, and South Africa, 2020. Issue 12 (2nd December 2020) - Olsen, Sonja J.; Azziz‐Baumgartner, Eduardo; Budd, Alicia P.; Brammer, Lynnette; Sullivan, Sheena; Pineda, Rodrigo F.; Cohen, Cheryl; Fry, Alicia M.
Abstract : Transplant recipients are among the groups for whom the updated recommendations for 2020–2021 influenza vaccination should generally be considered essential, notably in the face of the COVID‐19 pandemic.